Pengaruh jarak tanam dan pupuk kompos pada pertumbuhan dan hasil tanaman bawang merah - Catur Anggarayasa; Made Sri Yuliartini; Anak Agung Sagung Putri Risa Andriani (Fakultas Pertanian, Universitas Warmadewa, 2018)
The purpose of this study was to determine the effect of spacing and compost on the growth and yield of shallots and their interactions. This research is a factorial experiment with a basic design using a randomized block design (RBD) carried out in paddy fields located in Angseri Subak, Angseri Village, Baturiti District, Tabanan Regency. The results showed that the interaction between the treatment of spacing with compost had no significant effect on all observed variables. The highest fresh weight of tubers per clump was obtained at a spacing of 20 cm x 25 cm, which was 38.73 g, increasing by 30.93% compared to the lowest yield at a spacing of 20 cm x 10 cm, 26.75 g. The highest fresh weight of tuber per clump was obtained by giving 60 tons ha-1 compost which was 34.81 g, increasing by 11.50% when compared to the lowest yield in the treatment without compost ie 30.79 g.